Empirical testing of cryoconite granulation: Role of cyanobacteria in the formation of key biogenic structure darkening glaciers in polar regions - Wejnerowski, Łukasz; Poniecka, Ewa; Buda, Jakub; Klimaszyk, Piotr; Piasecka, Agnieszka; Dziuba, Marcin Krzysztof; Mugnai, Gianmarco; Takeuchi, Nozomu; Zawierucha, Krzysztof (Wiley, 2023)
Cryoconite, the dark sediment on the surface of glaciers, often aggregates into oval or irregular granules serving as biogeochemical factories. They reduce a glacier’s albedo, act as biodiversity hotspots by supporting aerobic and anaerobic microbial communities, constitute one of the organic matter (OM) sources on glaciers and are a feeder for micrometazoans. Although cryoconite granules have multiple roles on glaciers, their formation is poorly understood. Cyanobacteria are ubiquitous and abundant engineers of cryoconite hole ecosystems. This study tested whether cyanobacteria may be responsible for cryoconite granulation as a sole biotic element. Incubation of Greenlandic, Svalbard and Scandinavian cyanobacteria in different nutrient availability and substratum for the growth (distilled water alone, and water with either quartz powder, furnaced cryoconite without OM or powdered rocks from glacial catchment) revealed that cyanobacteria bind mineral particles into granules. The structures formed in the experiment resembled those commonly observed in natural cryoconite holes: they contained numerous cyanobacterial filaments protruding from aggregated mineral particles. Moreover, all examined strains were confirmed to produce extracellular polymeric substances (EPS), which suggest that cryoconite granulation is most likely due to EPS secretion by gliding cyanobacteria. In the presence of water as the only substrate for growth, cyanobacteria formed mostly carpet-like mats. Our data empirically prove that EPS-producing oscillatorialean cyanobacteria isolated from the diverse community of cryoconite microorganisms can form granules from mineral substrate and that the presence of the mineral substrate increases the probability of the formation of these important and complex biogeochemical microstructures on glaciers.
This is the peer reviewed version of the following article: [Wejnerowski Ł., Poniecka E., Buda J., Klimaszyk P., Piasecka A., Dziuba M.K., Mugnai G., Takeuchi N., Zawierucha K. 2023. Empirical testing of cryoconite granulation: Role of cyanobacteria in the formation of key biogenic structure darkening glaciers in polar regions. Journal of Phycology 59: 939-949], which has been published in final form at [https://doi.org/10.1111/jpy.13372]. All data generated during and/or analysed during the current study are available in the manuscript and supplementary materials. Supplementary materials can be found online [https://doi.org/10.1111/jpy.13372] in the Supporting Information section at the end of the article.
Keywords: alcian blue staining; biogenic aggregations; cryoconite granules; extracellular polymeric substances; glacial ecosystems; glacier cyanobacteria; Microcoleus; Oscillatoriales; Phormidesmis; scanning electron microscopy